Education in Management of Siak Woven Fabrics by the DEKRANASDA - Aulia Annisa Fitri; Agusti Efi (Postgraduate School, Universitas Negeri Padang, 2022)
This study aims to determine the management of the Siak typical cloth carried out or managed by the Regional National Crafts Council (DEKRANASDA) in Siak Regency, Riau Province. The research used a qualitative approach and was conducted at DEKRANASDA in Siak Regency. Primary data were obtained from interviews with three weavers working in the DEKRANASDA Siak Regency, and interviews with two administrators from Dekranasda. The data obtained are further analyzed qualitatively. The Siak Woven Cloth Management Program is carried out by the DEKRANASDA by implementing or providing training for craftsmen who want to learn and carry out activities and events that can promote these crafts and cultural heritage to the community both inside and outside the Siak regency. the management carried out by the management for weavers who work in the DEKRANASDA Siak Regency is to provide raw materials, and equipment for weavers, and make new motifs, innovations, and color modifications but do not eliminate the characteristics of the Weaving itself and accommodate woven fabrics woven by independent or private craftsmen, promote MSME products through events and activities either directly as well as social media, marketing and paying for woven products according to the amount of woven fabric to craftsmen, providing facilities to weaving craftsmen, and making new products from Siak Weaving fabrics.